2008
DOI: 10.1097/pas.0b013e3181452176
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin Expression in the Differential Diagnosis of Human Ameloblastoma and Keratocystic Odontogenic Tumor

Abstract: Ameloblastoma is a benign, locally aggressive epithelial odontogenic tumor that has the potential to become malignant and produce metastasis to distant sites such as lungs and kidneys. The histologic presentation can be, in some instances, mistaken for keratocystic odontogenic tumor (KCOT) (formerly known as odontogenic keratocyst). The expression of calretinin [calbindin2 (CALB2)] was investigated on both ameloblastoma and KCOT. Nineteen cases of ameloblastoma and 17 cases of KCOT were stained with calretinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 23 publications
4
31
1
1
Order By: Relevance
“…Interestingly, calretinin appears to be a specific immunohistochemical marker for neoplastic ameloblastic epithelium since it has been identified in 93.5 % of multicystic and 81.5 % of unicystic ameloblastomas [2] but not in odontogenic cysts [3]. In the study by DeVilliers et al [4] comparing the calretinin immunohistochemical profile of ameloblastomas and OKCs (KCOTs), it was concluded that all (19/19) ameloblastomas were positive in contrast to 0/17 of the OKCs (KCOTs). Similarly, Anandani et al [5] detected immunopositivity for calretinin in 16/20 ameloblastomas but only in 1/20 OKCs (KCOTs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, calretinin appears to be a specific immunohistochemical marker for neoplastic ameloblastic epithelium since it has been identified in 93.5 % of multicystic and 81.5 % of unicystic ameloblastomas [2] but not in odontogenic cysts [3]. In the study by DeVilliers et al [4] comparing the calretinin immunohistochemical profile of ameloblastomas and OKCs (KCOTs), it was concluded that all (19/19) ameloblastomas were positive in contrast to 0/17 of the OKCs (KCOTs). Similarly, Anandani et al [5] detected immunopositivity for calretinin in 16/20 ameloblastomas but only in 1/20 OKCs (KCOTs).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sections were evaluated and the epithelial features were consistent in all sections. Be that as it may, to further investigate the possibility of ameloblastoma, multiple sections were immunohistochemically assessed for calretinin which can be identified in ameloblastomas but not in odontogenic cysts [2][3][4][5]. Besides calretinin, and in order to erase any doubt regarding the fibroblastic origin of spindle cells in the subepithelial induction-like zone, immunohistochemical staining for S100 protein and smooth muscle actin (SMA) were performed.…”
Section: Case Reportmentioning
confidence: 99%
“…CD56 expression was seen in the cytoplasm of peripheral cells of the follicles faintly. Altini et al, reported expression of calretinin in 81.5% of unicystic ameloblastomas and 93.5% of multicystic ameloblastomas whereas no expression was seen in residual cysts, dentigerous cysts, and odontogenic keratocysts except for a study by Piattelli et al, were calretinin positivity was seen in the proliferating epithelium in Odontogenic keratocyst [7][8][9]. Careful surgical excision is the treatment of choice for BOC and conservative enucleation is contraindicated as the recurrence rate in BOC is around 34% [1], which is due to the difficulty in removing or failure to remove the entire multilocular lesion during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin, a 29 KDa protein, has been found to show positive expression in neoplastic proliferation of ameloblastic epithelium, specifically staining the stellate reticulumlike cells of ameloblastoma. [15][16][17] Calretinin is considered as an additional important marker to differentiate PA from IOBCC. tumors because of the differences in prognosis and potential differences in treatment.…”
Section: Basal Cell Ameloblastoma (Bca)mentioning
confidence: 99%